The Effect of Per Capita Income, Human Development Index and Open Unemployment Rate on Poverty in Tebo District - Astuti Prihatiningsih; Wahyu Aldino (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
This study aims to analyze the effect of per capita income, the human development index and the open unemployment rate on the poverty rate in Tebo District. The research method used is secondary data analysis method.The analytical tool used is multiple regression analysis. Based on the results of testing the regression equation model using Microsoft Excel Data Analyze, it is obtainedthe calculation results obtained are F-Count = 0.2767 while F-Table = 9.28 (α = 0.05; 3.2), so F-Count < F-Table. Comparison between F-Count and F-Table which shows that F-Count < F-Table, indicating that the independent variables together have no significant effect on the dependent variable, so that per capita income, HDI and open unemployment rate during the 2017-2021 period together -sama did not have a significant effect on the incidence of poverty in Tebo District.